A Japan compact bus terminal; Review on Hakata bus terminal, Fukuoka - Khosyiatillah Hakim; Bart Julien Dewancker; Usep Surahman (IPTEK Journal of Proceedings Series, 2017)
A mass transportation system has a main role in every development process of countries in the modern world. In Japan, transportation infrastructure such as train stations or bus terminals plays as an important node that determines the development of functions and other community activities in the surrounding area. Based on the compact city development concept, various types of transport infrastructure were constructed in the integrated area of city nodes and mixed with a various public and commercial functions and supported with a well-structured management of transportation systems. With the condition of limited land in the city nodes, transport infrastructure has to be built as a compact building. This paper reviews design and system of Bus Terminal in Japan from the architectural perspective with the issue of a compact building. As a study case, Hakata Bus terminal is one of Japanese bus terminal built with a slim building and vertically extended level without bus parking area. The platform was divided into three different floor levels with total ten building stories filled by various public and commercial functions. Time schedule, information system, people and vehicle circulation, and the other aspect become the main support to create a compact bus terminal. However, the commercial function is more prominent than the overall function of the building, thus making Hakata bus terminal does not show the typology terminal design in general. Overall, the terminal provides community services without ignoring the main function as a mass transportation system in a compact bus terminal.